Respostas

2014-02-15T00:19:01-02:00
A2 = a1 + r              a5 = a4 +r           a8 = a7 + r
a2 = 6 +(-4)             a5 = -6 -4            a8 = -18 -4
a2 = 2                     a5 = -10              a8 = -22

a3 = a2 + r              
a3 = 2 -4                 a6 = a5+r
a3 = -2                    a6 = -10 -4           logo a P.A = (6,2,-2,-6,-10,-14,-18,-22)
                              a6 = -14   

a4 = a3 + r              
a4 = -2 -4                 a7 = a6 + r
a4 = -6                    a7 = -14 -4
                              a7 = -18
1 5 1